Safe House App: Development of Mobile Application for Handling Household Emergency - Mohammed Zubil, Nurul Aida; Ahmad Zaki, Nadia Akma (International Journal of Recent Technology and Applied Science (IJORTAS), 2023)
Many people have a poor level of emergency preparedness, especially in their home environment. A previous study has stated that only a small percentage of people were well prepared in case of an emergency happening in their home while others are either do not know what to do or do not even think about it. This ignorance can lead to a harmful accident. For example, if an emergency such as a kitchen fire happens and is poorly handled by the people in the house it can lead to bigger accidents such as fire outbreaks. Thus, this study aims to identify the requirement, design, and develop a mobile application that can help users learn about household emergencies and increase their preparedness level for emergencies. Compared to other mobile applications for an emergency, Safe House App provides multimedia elements such as videos, and quiz activity which can attract users to use the application more to learn about the household emergency. The methodology implemented for this study is the Agile Model. Functionality Evaluation is conducted on 10 respondents aged 18 and above and most of the respondents are satisfied with the overall performance of Safe House App and agree that Safe House App can help the user increase their emergency preparedness level and attract them to learn about the household emergency.